Sustainability assessment of rural toilet technology based on the unascertained measure theory - Wu, Simei; Chai, Qing; Liu, Xiaojun; He, Bao-Jie (Frontiers in Environmental Science, 2023)
Upgrading toilets in rural areas is an effective way to protect public health and reduce environmental pollution. The study aims to build a sustainability evaluation model(RTSAM) of rural toilet technology to support the local government in improving rural toilets. The unconfirmed measure theory(UMT) is integrated into the model to quantify the sustainability performance of toilet technology in three dimensions: economy, environment, and service & management. A case study of Honghai Village, Inner Mongolia, China, is conducted to verify the reliability of RTSAM. The results show that the sustainability performance of the three-compartment septic tank toilets(TCSTT)technology is promising in Honghai Village. The results are consistent with the situation of toilet technology in the village, which verifies the model's validity. The results of this study can help local government upgrade rural toilets and improve the living standards of rural residents.